Mendorong Keunggulan Bersaing melalui Integrasi Strategi Bisnis Hijau dan Pemasaran Berkelanjutan: Studi pada UMKM Fesyen di Kabupaten Banyumas - Puspita Lianti Putri; Iin Dyah Indrawati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The increasing global awareness of environmental issues has driven significant changes in business strategies across various sectors, including micro, small, and medium enterprises (MSMEs). In the fashion sector, MSMEs are not only required to innovate in product design and quality, but also to integrate sustainability practices throughout the value chain, from production processes to marketing strategies. These practices include the use of environmentally friendly materials, energy efficiency, responsible waste management, and conveying sustainability values through brand communications. This study aims to analyze the influence of green business strategies and sustainable marketing on the competitive advantage of fashion MSMEs in Banyumas Regency, Indonesia. The research method used is a quantitative approach with a survey design of 100 fashion MSMEs selected based on the criteria of involvement in production and marketing activities for at least two years. The data collection instrument was a structured questionnaire that has been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the classical assumption test using SPSS software to examine the partial and simultaneous relationships between the independent and dependent variables. The results show that both green business strategies and sustainable marketing have a positive and significant effect on competitive advantage, both separately and simultaneously. The coefficient of determination (R²) of 0.52 indicates that the two variables are able to explain 52% of the variation in competitive advantage, while the remainder is influenced by other factors outside the research model. This finding confirms that the integration of internal (operational) and external (marketing) sustainability approaches is a strategic factor in strengthening the market position of MSMEs, especially in non-urban areas.